Cardiac surgery practice during the COVID-19 outbreak: a multicentre national survey. (28th February 2021) - Rubino, Antonino Salvatore; De Santo, Luca Salvatore; Pisano, Antonio; Mauro, Michele di; Benussi, Stefano; Borghetti, Valentino; Castiglioni, Alessandro; Chiariello, Luigi; Colli, Andrea; De Bellis, Antonio; De Filippo, Carlo Maria; De Paulis, Ruggero; et al.
Abstract:  : OBJECTIVES: Healthcare systems worldwide have been overburdened by the coronavirus disease 2019 (COVID-19) outbreak. Accordingly, hospitals had to implement strategies to profoundly reshape both non-COVID-19 medical care and surgical activities. Knowledge about the impact of the COVID-19 pandemic on cardiac surgery practice is pivotal. The goal of the present study was to describe the changes in cardiac surgery practices during the health emergency at the national level. METHODS: A 26-question web-enabled survey including all adult cardiac surgery units in Italy was conducted to assess how their clinical practice changed during the national lockdown. Data were compared to data from the corresponding period in 2019. RESULTS: All but 2 centres (94.9%) adopted specific protocols to screen patients and personnel. A significant reduction in the number of dedicated cardiac intensive care unit beds (−35.4%) and operating rooms (−29.2%), along with healthcare personnel reallocation to COVID departments (nurses −15.4%, anaesthesiologists −7.7%), was noted. Overall adult cardiac surgery volumes were dramatically reduced (1734 procedures vs 3447; P  < 0.001), with a significant drop in elective procedures [580 (33.4%) vs 2420 (70.2%)]. CONCLUSIONS: This national survey found major changes in cardiac surgery practice as a response to the COVID-19 pandemic. This experience should lead to the development of permanent systems-based plans to face possible future pandemics. These data may effectively help policy decision-making in prioritizing healthcare resource reallocation during the ongoing pandemic and once the healthcare emergency is over.